Ilustrasi Fenomena Kekerasan Seksual untuk Desain Motif Kemeja - AZZAHRA GEA FLORIAN; Felix Ari Dartono (Pusat Penerbitan LP2MPP ISI Denpasar, 2022)
Based on data collection belonging to the Ministry of Women's Empowerment and Child Protection, the phenomenon of sexual violence increased from 2019 to 2021. The concept of the phenomenon of sexual violence was raised to convey to the public that the impact experienced by victims of sexual violence was not only from the perpetrators but also from the words and stigma of the community looking down on them. victim. The method used in this design is the Palgunadi design process approach, namely, the exploration process, the extraction process, and the termination point. The exploration process, in this case the search for human behavior and sexual violence. Extraction Process, summarizes matters related to human behavior and sexual violence. Termination Point, the design plan is made based on human behavior in the phenomenon of sexual violence by interpreting animal behavior in the form of animals and inanimate objects, and using several paintings, events, and legends as a source of inspiration. The results of this design are 8 designs of which there are 3 designs that are realized into casual shirt products with the concept of the phenomenon of sexual violence visualized with illustration techniques.